2009
DOI: 10.1007/s00253-008-1756-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen supply on rtPA expression in Escherichia coli BL21 (DE3): ammonia effects

Abstract: In shake flasks, good oxygen supply tended to decrease rtPA expression in media containing only yeast extract and tryptone, while oxygen limitation would increase rtPA synthesis in the same medium. Our data showed that though the drop of rtPA expression in the 20-ml cultures of LBG or 2YTG was accompanied with a severe acetate accumulation, it was actually caused by low ammonia. The rtPA expression level could be significantly improved by increasing culture ammonium ion up to 500 mM. The effects of exogenous h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…The effects of varying the concentrations of yeast extract and bacto tryptone in TB were also investigated, but again no increases in SELP production levels were noted. Ammonium and amino acid additives were then examined as previous studies have indicated the positive effects of ammonium as a nitrogen source, even in the presence of excess organic nitrogen [32]. Furthermore, due to the highly repetitive nature of the amino acid sequences of PBPs, the potential benefits of exogenously added amino acids can be easily understood and has been previously shown.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of varying the concentrations of yeast extract and bacto tryptone in TB were also investigated, but again no increases in SELP production levels were noted. Ammonium and amino acid additives were then examined as previous studies have indicated the positive effects of ammonium as a nitrogen source, even in the presence of excess organic nitrogen [32]. Furthermore, due to the highly repetitive nature of the amino acid sequences of PBPs, the potential benefits of exogenously added amino acids can be easily understood and has been previously shown.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that recombinant protein expression in E. coli cells is decreased by acetate accumulation [5] , [6] . However, our previous study showed that acetate concentrations up to 200 mM had little effect on the protein expression of recombinant tissue plasminogen activator (rtPA) in this strain [2] .…”
Section: Introductionmentioning
confidence: 85%
“…The use of glucose or glycerol as the carbon source in a complex medium may result in acetate accumulation at high levels, often up to 50–100 mM, particularly in high-density fermentations [1] , [2] . In aqueous solution, the acetate anion (Ac – ) exists in equilibrium with the undissociated acetic acid (HAc) and their relative quantities depend on pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid pKD46 (Amp R ) was used as a helper plasmid for increasing the efficiency of homologous recombination, and pCP20 (Cm R /Amp R ) was used for eliminating the resistance marker of the mutants in the construction of leaky strains (Datsenko and Wanner, ). The plasmids pET32a‐ pth and pET22b‐ rpa , both constructed without signal sequences, were used for the expression of exogenous proteins Trx‐hPTH (a thioredoxin fusion protein used for its residence at the periplasmic space of E. coli ) (Bayer et al ., ; Fu et al ., ) and rPA (Wang et al ., ) in periplasmic space or in cytoplasm. The primers were designed by Primer Premier 5.0 and verified by Oligo 7.0.…”
Section: Methodsmentioning
confidence: 99%